LEGAL INTERVENTION BY THE COOPERATIVE UNIVERSITY OF COLOMBIAIN THE STUDY OF PROBLEMS OF THE VULNERABLE POPULATION IN THE REGION - Vargas Machado, Camilo Andrés (2024)
The document presented here is the preliminary product of a mixed investigation with a descriptive approach and interpretive paradigm developed in the period 2022 to 2023 by the Legal Office and Conciliation Center of the Faculty of Law, of the Campus of the Universidad Cooperativa de Colombia in the city of Santa Marta. Where participant observation was applied to develop the legal intervention, based on a methodological design that required the determination of persistent problems and emerging problems in the community of Barrio Once de Noviembre, of Locality 1 of the same city, which is the Capital from the Department from Magdalena in the republic of Colombia. With this, the appropriate protocols were developed according to ethical criteria and scientific integrity, to collect data applying the exploratory survey technique in a specific group of forty one young adolescent students from a Public-School Headquarters that is a District Educational Institution in the District of Santa Marta, in the Department of Magdalena in Colombia. Therefore, after a careful approach throughout 2022, exercises and activities were developed to disseminate and make the objective, purpose and impact of the research understood by all related participants. Comply with three specific objectives with which frequencies were consolidated that led to the generation of twenty-two key words and an equal number of codes that prioritized the problems determined from the students’ own discourse. Which in turn agreed to generate important recommendations to the Institutions, and conclusions that will allow the consolidation of a second stage of the project.